The development and validation of the Breast Lymphoedema Severity Symptom (BLYSS) questionnaire - Smith, Christine (Curtin University, 2013)
The emergence of breast conservation therapy, with reported increased rates of breast lymphoedema encouraged this study. Using a standardised approach and utilising an extensive literature review and key informants including clinical specialists and patients with breast lymphoedema, the BLYSS questionnaire was developed. Through an iterative process, the validity and reliability of the BLYSS questionnaire was established. In addition, a definition for breast lymphoedema was developed using a consensus approach and applied in the study.